Social Connections, Leukocyte Telomere Length, and All-Cause Mortality in Older Adults From Costa Rica: The Costa Rican Longevity and Healthy Aging Study (CRELES) - Gan, Danting (2025)
Objectives: To examine the association of social connections with blood leukocyte telomere length (LTL) and all-cause mortality in older Costa Ricans. Methods: Utilizing data from the Costa Rican Longevity and Healthy Aging Study (CRELES), a prospective cohort of 2827 individuals aged 60 and above followed since 2004, we constructed a Social Network Index (SNI) based on marital status, household size, interaction with non-cohabitating adult children, and church attendance. We used linear regression to assess SNI’s association with baseline LTL (N = 1113), and Cox proportional-hazard models to examine SNI’s relationship with all-cause mortality (N = 2735). Results: Higher SNI levels were associated with longer telomeres and decreased all-cause mortality during follow-up. Being married and regular church attendance were associated with 23% and 24% reductions of the all-cause mortality, respectively. Discussion: These findings underscore the importance of social engagement in promoting longevity among older Costa Ricans, suggesting broader implications for aging populations globally.